Homing behaviour by destructive crown-of-thorns starfish is triggered by local availability of coral prey. Issue 1938 (11th November 2020) - Ling, S. D.; Cowan, Z.-L.; Boada, J.; Flukes, E. B.; Pratchett, M. S.
Abstract : Corallivorous crown-of-thorns starfishes ( Acanthaster spp.) can decimate coral assemblages on Indo-Pacific coral reefs during population outbreaks. While initial drivers of population irruptions leading to outbreaks remain largely unknown, subsequent dispersal of outbreaks appears coincident with depletion of coral prey. Here, we used in situ time-lapse photography to characterize movement of the Pacific crown-of-thorns starfish ( Acanthaster cf. solaris ) in the northern and southern Great Barrier Reef in 2015, during the fourth recorded population outbreak of the starfish, but prior to widespread coral bleaching. Daily tracking of 58 individuals over a total of 1117 h revealed all starfish to move a minimum of 0.52 m, with around half of all tracked starfish showing negligible daily displacement (less than 1 m day −1 ), ranging up to a maximum of 19 m day −1 . Movement was primarily nocturnal and daily displacement varied spatially with variation in local availability of Acropora spp., which is the preferred coral prey. Two distinct behavioural modes emerged: (i) homing movement, whereby tracked paths (as tested against a random-walk-model) involved short displacement distances following distinct 'outward' movement to Acropora prey (typically displaying 'feeding scars') and 'homebound' movement to nearby shelter; versus (ii) roaming movement, whereby individuals showed directional movement beyond initial tracking positions without return. Logistic modelling revealed more than half of all tracked starfish demonstrated homing when local abundance (percentage cover) of preferred Acropora coral prey was greater than 33%. Our results reveal facultative homing by Acanthaster with the prey-dependent behavioural switch to roaming forays providing a mechanism explaining localized aggregations and diffusion of these population irruptions as prey is locally depleted.